The BDNF–TrkB–CREB Signalling Pathway Is Involved in Bisphenol S-Induced Neurotoxicity in Male Mice by Regulating Methylation - Yi-Zhou Li; Zi-Yao Wu; Bi-Qi Zhu; Yu-Xiao Wang; Ya-Qi Kan; Huai-Cai Zeng (Toxics, 2022)
Bisphenol S (BPS), the most common substitute for bisphenol A in manufacturing, is associated with neurotoxicity, but its molecular mechanisms are unclear. Here, we studied the role of the BDNF–TrkB–CREB (brain-derived neurotrophic factor–tropomyosin-related kinase B–CAMP response element-binding protein) signalling pathway in bisphenol S-induced neurotoxicity via methylation regulation in male C57BL/6 mice. The mice were treated with sesame oil or 2, 20 and 200 mg/kg body weight BPS for 28 consecutive days, and the hippocampus was extracted. We recorded the body weight, organ index, and hippocampal pathology and ultrastructure of the mice. The BDNF, TrkB, CREB, phosphorylated (p)-CREB, DNMTs (DNA methyltransferases) levels were determined by qRT-PCR and/or Western blotting. BDNF promoter IV methylation level was detected by bisulfite sequencing PCR. BPS damaged the mouse hippocampus ultrastructure and reduced the number of synapses. Further, it increased the methylation rate of BDNF promoter IV; downregulated BDNF, CREB, p-CREB/CREB and DNMT1 expression; and upregulated DNMT3a and DNMT3b expression. Therefore, we speculate that the BDNF–TrkB–CREB pathway may be involved in BPS-induced neurotoxicity in male mice by regulating methylation.